Pengaruh Motivasi, Pengetahuan, dan Fasilitas terhadap Kepatuhan Pemilahan Limbah Infeksius dan Non Infeksius dengan Sikap sebagai Mediator - Edward Marpaung, Yohan; Kusumapradja, Rokiah; Johanes, Johanes (Green Publisher Indonesia, 2025)
The background of this study is related to the lack of compliance in sorting infectious and non-infectious waste in nurses. This study was conducted to evaluate the perception of compliance in the separation of infectious and non-infectious waste at the Class C Private General Hospital in Central Lampung. The main focus is to analyze the influence of knowledge, work motivation, availability of facilities, on the perception of compliance in waste sorting by using attitude as a mediating variable. This research uses an analytical quantitative design with a cross-section design and a field research approach. The population used was hospital nurses with a sampling technique in the form of saturated sampling by making a total of 119 nurses as respondents. The data was collected using a questionnaire and then analyzed using the three box method and the SEM-PLS statistical method with the help of the SmartPLS-4 device. The results of this study show that there is a significant influence between work motivation and attitude on the perception of waste sorting compliance. On the other hand, there is a significant indirect influence between knowledge and work motivation on the perception of waste separation compliance when mediated by attitudes. Knowledge, work motivation and availability of facilities have a significant influence on attitudes. However, the attitude of not mediating the influence of facility availability on the perception of waste sorting compliance behavior Thus, the perception of compliance behavior in conducting waste sorting is significantly influenced by work motivation and attitude. Therefore, these factors need to be continuously improved to ensure effective medical waste management in the health environment.